Principles of engineering graphics - Giesecke, Frederick E. (Frederick Ernest) 1869-1953; Mitchell, Alva; Spencer, Henry Cecil; Hill, Ivan Leroy; Loving, Robert Olin; Dygdon, John Thomas; Novak, James E. (Macmillan Pub. Co. ; Maxwell Macmillan Canada ; Maxwell Macmillan International, 1994)
Based on the latest edition of Engineering Graphics, the second edition of Principles of Engineering Graphics is a combination textbook/workbook that provides students with a dynamic and up-to-date learning tool at an affordable price. The high quality illustrations and problems that made Engineering Graphics the definitive text in its field for over two decades have been incorporated in Principles of Engineering Graphics, Second Edition. Chapters on computer graphics cover the latest equipment and procedures in computer-aided drafting and design. Examples based on several of the most popular CAD software programs and many illustrations of computer-generated drawing are included as well. Principles of Engineering Graphics, Second Edition, consistently reflects CAD/CAM trends and the latest ANSI standards. Chapters on manufacturing processes, dimensioning, tolerancing, and threads and fasteners have been extensively reviewed and updated to ensure their conformity with the latest standards.